Simplifying the Welfare Quality® assessment protocol for broiler chicken welfare. (26th August 2015) - de Jong, I. C.; Hindle, V. A.; Butterworth, A.; Engel, B.; Ferrari, P.; Gunnink, H.; Perez Moya, T.; Tuyttens, F. A. M.; van Reenen, C. G.
Abstract : Welfare Quality ® (WQ) assessment protocols place the emphasis on animal-based measures as an indicator for animal welfare. Stakeholders, however, emphasize that a reduction in the time taken to complete the protocol is essential to improve practical applicability. We studied the potential for reduction in time to complete the WQ broiler assessment protocol and present some modifications to the protocol correcting a few errors in the original calculations. Data was used from 180 flocks assessed on-farm and 150 flocks assessed at the slaughter plant. Correlations between variables were calculated, and where correlation was moderate, meaningful and promising (in terms of time reduction), simplification was considered using one variable predicted from another variable. Correlation analysis revealed a promising correlation between severe hock burn and gait scores on-farm. Therefore, prediction of gait scores using hock burn scores was studied further as a possible simplification strategy (strategy 1). Measurements of footpad dermatitis, hock burn, cleanliness and gait score on-farm correlated moderately to highly with slaughter plant measurements of footpad dermatitis and/or hock burn, supporting substitution of on-farm measurements with slaughter plant data. A simplification analysis was performed using footpad dermatitis, hock burn, cleanliness and gait scores measured on-farm predicted from slaughter plant measurements of footpad dermatitis and hock burn (strategy 2). Simplification strategies were compared with the full assessment protocol. Close agreement was found between the full protocol and both simplification strategies although large confidence intervals were found for specificity of the simplified models. It is concluded that the proposed simplification strategies are encouraging; strategy 1 can reduce the time to complete the on-farm assessment by ~1 h (25% to 33% reduction) and strategy 2 can reduce on-farm assessment time by ~2 h (50% to 67% reduction). Both simplification strategies should, however, be validated further, and tested on farms with a wide distribution across the different welfare categories of WQ.